2022
DOI: 10.3758/s13414-022-02568-2
|View full text |Cite
|
Sign up to set email alerts
|

Task cue influences on lexical decision performance and masked semantic priming effects: The role of cue-task compatibility

Abstract: Recent research demonstrated that mere presentation of a task cue influences subsequent unconscious semantic priming by attentional sensitization of related processing pathways. The direction of this influence depended on task-set dominance. Dominant task sets with a compatible cue-task mapping were supposed to be rapidly suppressed, while weak task sets showed more sustainable activation. Building on this research, we manipulated cue-task compatibility as instance of task-set dominance in two experiments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…In induction tasks 2 Behavioral data suggested that participants always prepare for an induction task after presentation of the cue. If instead the LDT followed (task cue-only trial), participants had to suppress the prepared cognitive state for the cued induction task and first re-activate the required task demands for the LDT (Berger et al, 2022). Accordingly, it is not surprising that pre-stimulus differences between outliers and valid trials were more pronounced in induction tasks, as preparatory processes were qualitative different between both trial types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In induction tasks 2 Behavioral data suggested that participants always prepare for an induction task after presentation of the cue. If instead the LDT followed (task cue-only trial), participants had to suppress the prepared cognitive state for the cued induction task and first re-activate the required task demands for the LDT (Berger et al, 2022). Accordingly, it is not surprising that pre-stimulus differences between outliers and valid trials were more pronounced in induction tasks, as preparatory processes were qualitative different between both trial types.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, except of the cues "rund"/"belebt", each cue could indicate each decision category. While this manipulation was of theoretical interest for the work by (Berger et al, 2022), it is of no particular interest concerning the within-subject comparison of valid and outlier trials in the present article. For the purpose of the nature of the task cues as well as information about the stimulus material, practice trials and the prime identification task please refer to (Berger et al, 2022).…”
Section: Paradigmmentioning
confidence: 97%
See 3 more Smart Citations